2015
DOI: 10.1890/14-1985.1
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term changes in liana loads and tree dynamics in a Malaysian forest

Abstract: Abstract. The importance of lianas through time and their effect on tree reproduction are evaluated for the first time in a Southeast Asian Dipterocarp forest. We quantified flower and seed production by lianas and trees for 13 years, assessed liana loads in the crowns of all trees larger than 30 cm in diameter at breast height (1.3 m) in 2002 and 2014, and assessed levels of reproduction for the same trees during a strong general flowering event in 2014 for the 50-ha forest dynamics plot at the Pasoh Forest R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
99
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(106 citation statements)
references
References 51 publications
7
99
0
Order By: Relevance
“…Liana density is highest in tropical South America, followed by Africa, Central America, and Asia (462, 374, 351 and 223 individuals/ha, respectively), whereas diversity is highest in Africa followed by South America, Central America, and lastly Asia (Fisher's α of 26.0, 15.5, 12.1 and 6.6, respectively; DeWalt et al 2015). The trees of this family are typical emergent with few low branches, and lianas have a lower probability of occurrence in their crowns (Wright et al 2015). Lianas outcompeting trees might therefore be a regular and repeatable observation in Neotropical forests, through a product of the interaction between tree and liana community composition and structure that is absent from other tropical regions.…”
Section: Cube Root Growth In Dbhmentioning
confidence: 99%
See 1 more Smart Citation
“…Liana density is highest in tropical South America, followed by Africa, Central America, and Asia (462, 374, 351 and 223 individuals/ha, respectively), whereas diversity is highest in Africa followed by South America, Central America, and lastly Asia (Fisher's α of 26.0, 15.5, 12.1 and 6.6, respectively; DeWalt et al 2015). The trees of this family are typical emergent with few low branches, and lianas have a lower probability of occurrence in their crowns (Wright et al 2015). Lianas outcompeting trees might therefore be a regular and repeatable observation in Neotropical forests, through a product of the interaction between tree and liana community composition and structure that is absent from other tropical regions.…”
Section: Cube Root Growth In Dbhmentioning
confidence: 99%
“…Caballe and Martin (2001) observed a 20% decrease in liana density, compared to 5% decrease in tree density in a Gabonese semideciduous forest. A single study has analysed long-term liana dynamics in Southeast Asia, again reporting a decrease in the proportion of large trees colonized by lianas over a 10-yr period from an aseasonal tropical forest in Peninsula Malaysia (Wright et al 2015). Thomas et al (2015) observed a 16% decrease in liana density over a 10-yr period in Korup National Park, Cameroon; a forest experiencing a 3-month dry season with mean monthly precipitation <100 mm.…”
Section: Cube Root Growth In Dbhmentioning
confidence: 99%
“…In contrast, smaller understory growth forms tend to have shallower root systems and to be more susceptible to changes in water availability (Becker & Castillo, 1990;Opler, Frankie, & Baker, 1980;Wright, 1991). As another example, woody vines or lianas are a characteristic feature of tropical forests (Gentry, 1991) and are increasing in importance in many Neotropical forests (reviewed by Schnitzer & Bongers, 2011;Wright, Sun, Pickering, Fletcher, & Chen, 2015). As another example, woody vines or lianas are a characteristic feature of tropical forests (Gentry, 1991) and are increasing in importance in many Neotropical forests (reviewed by Schnitzer & Bongers, 2011;Wright, Sun, Pickering, Fletcher, & Chen, 2015).…”
mentioning
confidence: 99%
“…This increase in liana abundance may enhance the negative impacts on tree demographic rates (i.e. reproduction, regeneration, growth and survival) in aseasonal and seasonal tropical forests alike (Magrach et al., ; Wright, Sun, Pickering, Fletcher, & Chen, ). Although the effect of lianas on forest dynamics has been studied in more seasonal tropical forests (Estrada‐Villegas & Schnitzer, ; Van der Heijden, Powers, & Schnitzer, ), empirical support for the effect of lianas on tree growth and survival remains limited in aseasonal forests of Southeast Asia, which are important biodiversity hotspots of both flora and fauna (Estrada‐Villegas & Schnitzer, ; Myers, Fonseca, Mittermeier, Fonseca, & Kent, ; Wright, Sun, et al., ).…”
Section: Introductionmentioning
confidence: 99%